Transformational Leadership and Stakeholder Management in Library Change - Sucozhañay, Dolores; Siguenza-Guzman, Lorena; Zhimnay, Cristian; Cattrysse, Dirk; Wyseure, Guido; De Witte, Karel; Euwema, Martin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
This article aims to analyse the role of library managers as change agent when implementing Library 2.0, using transformational leadership and stakeholder management approaches. To do so, a case study in a Latin American academic library was performed. The experiences acquired for a period of six years were analysed, during which three library managers were involved in managing change. Qualitative data from documents, interviews, and observations were collected, and qualitative analysis methods were used to obtain in-depth understanding of the change process. Results show that lack of transformational leadership and stakeholder management contribute to delayed implementation and limited adoption of innovations. Although library managers recognized the importance of different stakeholders to implement changes, they did not apply systematic and proactive strategies to define and manage them. All in all, library managers should be trained as change agents, with emphasis on transformational leadership and stakeholder management skills.